Larval ecomorphology of 13 Libellulidae (Anisoptera, Odonata) of the Middle Rio Doce Valley, Minas Gerais, Brazil - Giacomini,HC. (2008)
In the lakes of the Middle Rio Doce, Minas Gerais (MG), two groups of larval Libellulidae are distinguished by preferences of habitat use: one uses mainly aquatic macrophytes and the other uses the bottom substrate. The goal of this work was to verify if there is a morphological distinction between the two groups of species. Thirteen body measures were taken from the larvae and analyzed. No difference was found between the two groups of species regarding the body size, but shape differences were observed for two morphological variables. The species that use mainly macrophytes tend to have larger relative measures of the labium and smaller measures of the abdomen width. Advantages in resource obtainment and in vulnerability to predation are probably the explanations for the morphological divergence among these larval groups.